Influence of Work Discipline, Career Development and Job Satisfaction on Employee Performance Directorate General Research and Development of Ministry Research, Technology and Higher Education (International Journal of Scientific Research and Management (IJSRM), 2018)
This causal research aims to find out information about possible employee performance that is influenced by work discipline, career development, and job satisfaction.The survey method used in this study is data that has been analyzed by path analysis after all variables are incorporated into the correlation matrix. Data were collected from 113 employees as randomly selected samples.The result of the research found that: (1) work discipline has a positive effect on employee performance, (2) career development have positive effect on employee performance, (3) job satisfaction have positive effect to employee’s performance, (4) work discipline has positive effect to job satisfaction, 5) career development has a positive effect on job satisfaction, and (6) work discipline has a positive effect on career development.The results showed that work discipline, career development, and job satisfaction are the determinants of employee performance